Protocol for the trismus trial—therabite versus wooden spatula in the amelioration of trismus in patients with head and neck cancer: randomised pilot study. Issue 3 (30th March 2018) - Lee, Rana; Molassiotis, Alex; Rogers, Simon N; Edwards, Rhiannon Tudor; Ryder, David; Slevin, Nick
Abstract : Introduction: Patients can develop trismus from their head and neck cancer or as a result of treatment. Trismus affects the jaw muscles and makes mouth opening difficult. To potentially combat trismus, patients could undertake proactive jaw stretching exercises prior to, during and after radiotherapy, although currently these are not the standard of care. Methods and analysis: This is a randomised, open-label, controlled, two-centre feasibility study, to assess the objective and subjective effectiveness and cost-effectiveness of therabite use compared with wooden spatula in ameliorating trismus in patients treated for stage 3 and 4 oral and oropharyngeal cancer, managed either by primary surgery followed by (chemo)radiotherapy or primary (chemo)radiotherapy. The principal objective assessment is measurement of maximum jaw opening. Assessments in all cases will be performed preradiotherapy and again at 3 and 6 months postintervention. Secondary aims of the study will be (1) to assess whether therabite or the wooden spatula intervention improves patients' quality of life, (2) reduce the level of post-treatment clinical management/healthcare use and (3) a nested qualitative study will explore the experience of the patient taking part in the intervention; data will be transcribed verbatim and analysis will be based on content analysis methods using the interview questions as the framework for examination. Ethics and dissemination: North West Greater Manchester granted ethical approval (REC Reference 11/NW/0744). Good Clinical Practice and the Declaration of Helsinki have been adhered to. The results will be presented internationally and submitted to a peer-reviewed journal. Head and neck cancer charities and information websites will also be approached. Trial registration number: NCT01733797 .